Optimization of biodiesel production from waste cooking oil using Fe-Montmorillonite K10 by response surface methodology - Yahya S.; Muhamad Wahab S.K.; Harun F.W. (Elsevier Ltd, 2024)
Renewable Energy Volume 157, September 2020, Pages 164-172